An Alternative Splicing Switch Regulates Embryonic Stem Cell Pluripotency and Reprogramming - Gabut, Mathieu; Samavarchi-Tehrani, Payman; Wang, Xinchen; Slobodeniuc, Valentina; O'Hanlon, Dave; Sung, Hoon-Ki; Alvarez, Manuel; Talukder, Shaheynoor; Pan, Qun; Mazzoni, Esteban O.; Nedelec, Stephane; Wichterle, Hynek; et al. (Cell, 2011)
Alternative splicing (AS) is a key process underlying the expansion of proteomic diversity and the regulation of gene expression. Here, we identify an evolutionarily conserved embryonic stem cell (ESC)-specific AS event that changes the DNA-binding preference of the forkhead family transcription factor FOXP1. We show that the ESC-specific isoform of FOXP1 stimulates the expression of transcription factor genes required for pluripotency, including OCT4, NANOG, NR5A2, and GDF3, while concomitantly repressing genes required for ESC differentiation. This isoform also promotes the maintenance of ESC pluripotency and contributes to efficient reprogramming of somatic cells into induced pluripotent stem cells. These results reveal a pivotal role for an AS event in the regulation of pluripotency through the control of critical ESC-specific transcriptional programs. [Display omitted] ► An ESC-specific splicing switch in FOXP1 transcripts produces the FOXP1-ES isoform ► FOXP1-ES has distinct DNA-binding properties compared to the canonical FOXP1 isoform ► FOXP1-ES stimulates key pluripotency genes and represses many differentiation genes ► FOXP1-ES is required for ESC pluripotency and efficient iPSC reprogramming Alternative splicing produces an ESC-specific isoform of FOXP1 that represses genes responsible for differentiation and directly stimulates production of pluripotency genes, including Oct4 and Nanog